Deskripsi Kesulitan Belajar Matematika Siswa pada Materi Bangun Datar Ditinjau dari Segi Kemampuan Koneksi Matematika Siswa - Asdar; Fajar; Rahmawati (Program of Mathematics Education Department of Mathematics Faculty of Mathematics and Natural Sciences (FMIPA) Universitas Negeri Makassar (UNM), 2021)
This research aims to know the description of students' learning difficulties in learning mathematics on the topik of Plane viewed from students' mathematical connection ability. This research is descriptive research using a qualitative approach. Retrieval of the subject is formed by providing mathematical connection ability tests to students of class VIII and from the result of mathematical connection ability selected purposively 5 subjects. The instrument in this research is the test of mathematics connection ability, a diagnostik test of mathematics learning difficulties, and interview guidelines. Students' learning difficulties analyzed base on 5 indicators of learning difficulties, it contains abnormality of visual perception, interference of spatial relation, the association of visual-motor, difficulty in understanding symbol, difficulty in language and reading. The results showed that (1) subject with very good mathematical connection ability feel difficult in interference of spatial relation, (2) subject with good mathematical connection ability find difficulties in interference of spatial relation and association of visual-motor, (3) subject with moderate mathematical connection ability find difficulties in abnormality of visual perception, interference of spatial relation and association of visual-motor, (4) subject with low mathematical connection ability find difficulties in interference of spatial relation, association of visual-motor, abnormality in visual perception, difficulty in language and reading, (5) subject with very low mathematical connection ability experience difficulties in all the indicators of learning difficulties.